Changes on the Development of Rigor Mortis in Cultured Tilapia (Oreochromis niloticus) Fed with a Mixture of Plant Proteins - Nathaly Montoya Camacho; Enrique Márquez Ríos; Francisco Javier Castillo Yáñez; Saúl Ruíz Cruz; Aldo Alejandro Arvizu Flores; Wilfrido Torres Arreola; Jose Luis Cárdenas López; Santiago Valdéz Hurtado; Víctor Manuel Ocaño Higuera (Journal of Chemistry)
In recent years it has been pointed out that the feed of farmed fish has an effect on the quality of the final product. Therefore, this study evaluated the effect of fishmeal (FM) replacement by a mixture of plant protein (MPP) on the development of rigor mortis of tilapia (Oreochromis niloticus). One hundred and twenty fish at an initial average weight of 123 ± 6.3 g were fed with three extruded isonitrogenous and isolipidic 6.2% crude lipids experimental diets, in which FM were replaced by 0% (D0), 50% (D50), and 100% (D100) of MPP (soybean meal, corn meal, wheat meal, and sorghum meal). A reference diet (DC) containing FM as the main protein source was used as a control. The fish were divided into triplicate groups per dietary treatment. The experiment was conducted in a tank system at 26.8°C water temperature for 67 days. The chemical composition of experimental diets and muscle were determined. The glycogen, adenosine 5′-triphosphate (ATP) and related compounds, pH, shear force, and rigor index (RI%) were monitored during storage on ice for 48 h. The results indicated that FM replacement affected (p≤0.05) the muscle composition, where the fish fed with D100 presented the higher content of lipids and ash. Fish fed with D0 and DC presented a more pronounced onset of rigor mortis and also showed a higher IR%, a lower content of glycogen, ATP, adenosine 5′-diphosphate (ADP), adenosine 5′-monophosphate (AMP), pH, and shear force. The changes in chemical composition of muscle and other parameters evaluated indicated that FM replacement increases energy reserves (glycogen, ATP, ADP, and AMP) which delayed the onset of rigor mortis, as well as a lower pH and shear force in the muscle of tilapia. Therefore, the substitution of FM by MPP could contribute to delaying the onset of rigor mortis and with this, the quality and shelf life of tilapia could be increased.